(untitled) (The Pakistan Development Review, 1994)
The debt neutrality hypothesis, in its quintessential form, postulates that debt/tax mix for fmancing deficit is irrelevant. More precisely, the debt-neutrality deals with the two fundamental questions: (i) Given the volume and composition of government expenditures, does it matter whether they are fmanced by taxes or debt issue? (ii) Do public deficits absorb private savings that otherwise fmance private capital formation? Juxtaposed to the traditional Keynesian theory which answers these questions positively, the exponents of debt-neutrality make the counter-claim that debt is neutral and public deficits have no "crowding out" effects on private saving or investment. The debt-neutrality is popularly termed as the Ricardian Equivalence Hypothesis because the fundamental logic underlying this hypothesis was originally presented by David Ricardo in Chapter XVII entitled "Taxes on Other Commodities than Raw Produce" of his celebrated "The Principles of Political Economy and Taxation". Although Ricardo explained why government borrowing and taxes could be equivalent, he never sponsored the case for unlimited issue of government bonds. In fact, he warned against the consequences of continuous fiscal deficits in the following words: "Form what I have said, it must not be inferred that I consider the system of borrowing as the best calculated to defray the extraordinary expenses.....................